Preoperative Lund‐Mackay computed tomography score is associated with preoperative symptom severity and predicts quality‐of‐life outcome trajectories after sinus surgery. Issue 6 (8th March 2018) - Brooks, Steven G.; Trope, Michal; Blasetti, Mariel; Doghramji, Laurel; Parasher, Arjun; Glicksman, Jordan T.; Kennedy, David W.; Thaler, Erica R.; Cohen, Noam A.; Palmer, James N.; Adappa, Nithin D.
Abstract : Background: Disagreement exists about the relationship between Lund‐Mackay CT scores (LMCTS) and quality‐of‐life outcome (QoL) measures. We investigated whether preoperative LMCTS are associated with preoperative QoL, and whether LMCTS is predictive of postoperative QoL outcomes in chronic rhinosinusitis (CRS) patients. Methods: Adult patients with medically recalcitrant CRS (n = 665) were enrolled in a prospective, observational cohort study. Preoperative LMCTS and pre‐ and postoperative self‐reported QoL outcomes (22‐item Sino‐Nasal Outcomes Test [SNOT‐22]) were collected and evaluated over 12 months. Five hundred sixty‐eight patients met the inclusion criteria. Longitudinal linear mixed‐effects modeling was used to investigate the effect of LMCTS on QoL after functional endoscopic sinus surgery (FESS). Results: Preoperative LMCTS were significantly associated with preoperative SNOT‐22 scores ( p < 0.01) and postoperative SNOT‐22 scores ( p < 0.001), driven by Extranasal and Rhinologic subdomains of the QoL questionaire. Patients in the lowest preoperative LMCTS quartile had the lowest mean change in SNOT‐22 scores at 12 months (16.8 points; 95% confidence interval [CI], 12.2‐21.3). Patients in the second and third lowest preoperative LMCTS quartiles had mean changes at 12 months of 21.1 points (95% CI, 16.7‐25.4) and 23.1 points (95% CI, 18.3‐27.9). Patients in the highest preoperative LMCTS quartile had the greatest improvement in SNOT‐22 scores after FESS (29.9 points; 95% CI, 24.9‐34.8). The difference in QoL change at 12 months between the highest and lowest preoperative LMCTS quartiles was 13.1 points (95% CI, 6.0‐20.2; p < 0.001). Conclusion: Our study demonstrates that preoperative LMCTS correlate with preoperative extranasal and rhinologic symptom severity and that the LMCTS is an indicator of postsurgical QoL outcomes for medically recalcitrant chronic rhinosinusitis patients in a large tertiary otolaryngology setting.